The Book Out of Bounds: Essays Presented to Lars Ole Sauerberg - Schatz-Jacobsen, Claus; Simonsen, Peter; Pettitt, Tom (Aktualitet - Litteratur, kultur og medier, 2015)
Claus Schatz-Jacobsen, Peter Simonsen og Tom Pettitt, Institut for Kulturvidenskaber, Syddansk Universitet: "The Book Out of Bounds: Essays Presented to Lars Ole Sauerberg", marts 2015